Pengembangan Bahan Ajar Aqidah Ahklak di Madrasah Tsyanawiyah Hidayaturrahman NW Menggala (Suatu Pendekatan Studi Literatur) - Sahari Sahari (Universitas Pendidikan Mandalika, 2022)
This study aims to develop a discussion of Aqidah Akhlak in Madrasah Tsanawiyah Hidayaturrahman NW Menggala, North Lombok Regency by using the literature study method. The data sources of this research used secondary sources which were collected through textbooks, e-books, periodicals, laws and regulations, websites, and other relevant sources which were then analyzed descriptively. The results of this study are Aqidah Akhlak teaching materials which are arranged in accordance with the demands of the curriculum by considering the needs of students, namely teaching materials that are in accordance with the characteristics and settings or social environment of students. In addition, the development of teaching materials is expected to assist students in obtaining alternative teaching materials in addition to textbooks which are sometimes difficult to obtain and make it easier for teachers to carry out their duties as educators.